THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND MEDICATION ADHERENCE AMONG WORKERS WITH PULMONARY TUBERCULOSIS AT THE MEKAR MUKTI COMMUNITY HEALTH CENTER - Suriya, Melti; Pri Andini, Sisca; Zuriati, Zuriati; Sarifudin, Sarifudin (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2026)
Aim: To determine the relationship between family support and medication adherence among pulmonary tuberculosis workers undergoing treatment in the working area of Puskesmas Mekar Mukti. The study aims to examine whether the level of family support (emotional, informational, instrumental, and appraisal support) influences patients’ adherence to taking Anti-Tuberculosis Drugs (OAT). Methods: This study employed an analytical quantitative design with a cross-sectional approach. The sample consisted of 38 respondents selected using accidental sampling. Research instruments included a family support questionnaire and the Medication Adherence Rating Scale (MARS). Data were analyzed univariately and bivariately using the Chi-square test. Results: The univariate analysis showed that family support was equally distributed between good (19 respondents, 50%) and poor (19 respondents, 50%), while medication adherence was high in 20 respondents (52.6%). The bivariate analysis yielded a p-value of 0.023 (p < 0.05). Conclusion: There is a significant relationship between family support and medication adherence, as indicated by a p-value of 0.023 (p < 0.05). Patients with good family support were more likely to demonstrate high adherence compared to those with low support. This emphasizes that the family is an important factor in the success of TB therapy, particularly as treatment supervisors, reminders, companions in managing side effects, and sources of motivation.